Real world outcomes with alpelisib in metastatic hormone receptor-positive breast cancer patients: A single institution experience - Alaklabi, Sabah; Roy, Arya Mariam; Attwood, Kristopher; George, Anthony; O’Connor, Tracey; Early, Amy; Levine, Ellis G.; Gandhi, Shipra (Frontiers in Oncology, 2022)
Background: It is critically important to study the real-world data of FDA-approved medications to understand the response rates and toxicities observed in the real-world population not represented in the clinical trials. Methods: We reviewed charts of patients diagnosed with metastatic, hormone receptor-positive, human epidermal growth factor receptor 2 negative, PIK3CA-mutated breast cancer treated with alpelisib from May 2019 to January 2022. Clinical characteristics and treatment outcomes were collected. The association of clinical characteristics with responses and adverse events (AEs) was evaluated using the logistic regression model. Results: 27 patients were included. Median age at alpelisib initiation 67 years (range: 44, 77 years). Majority of patients had excellent performance status at time of alpelisib initiation. Most patients had chronic comorbidities, notably; 2 patients had controlled type 2 diabetes mellitus at time of alpelisib initiation. Majority had a median of three lines of therapy (range: 1, 7) before alpelisib. Clinical responses were determined using RECIST v1.1. 3/27 (11.11%) patients discontinued therapy before response assessment due to grade 3 AEs. Overall response rate was 12.5% (3/24), with all partial responses (PR). The median duration of response was 5.77 months (range: 5.54, 8.98). 14/27 (51.9%) of patients required dose interruption/reduction. Overall, 23/27 (85.19%) patients discontinued alpelisib of which 11 (47.83%) discontinued alpelisib due to AEs. Median duration of treatment was 2 months in patients who had grade 3 AEs (range: <1.00, 8.30) and 6.28 (1.15, 10.43) in those who did not. Any grade AEs were reported in 24/27 (88.9%) patients, namely, hyperglycemia 16/27 (59.3%), nausea 11/27 (40.7%), diarrhea 10/27 (37.0%), fatigue 7/27 (25.9%) and rash 6/27 (22.2%). Grade 3 AEs were reported in 13/27 patients (50%), namely, hyperglycemia in 7/27 (53.8%) patients followed by skin rash 4/27 (30.8 %), GI side effects 3/27 (23.1%). Those with progressive disease as best response to alpelisib, had more non-metabolic comorbidities, higher number of liver metastases, PIK3CA E545K mutations, and shorter duration on therapy compared to those with PR and stable disease. Conclusion: Patients should be counseled about the toxicity and modest benefit observed with alpelisib in real-world clinical practice when used in later lines of therapy.